Erythrodermic Psoriasis Causing Uric Acid Crystal Nephropathy - John Ellis; Jeffrey Lew; Sumir Brahmbhatt; Sarah Gordon; Troy Denunzio (Case Reports in Medicine)
Background. Erythrodermic psoriasis is a rare and severe variant of psoriasis. It is characterized by widespread skin erythema, scaling, pustules, or exfoliation of more than 75% of the body’s surface area. This condition has life-threatening complications to include hemodynamic, metabolic, immunologic, and thermoregulatory disturbances. One metabolic complication, hyperuricemia, occurs from rapid keratinocyte differentiation and infiltration of inflammatory cells into psoriatic lesions. Although renal injury caused by shunting of blood to the skin has been reported, there are no reports of erythrodermic psoriasis causing crystal-induced nephropathy. We present a case of erythrodermic psoriasis and hyperuricemia complicated by uric acid crystal nephropathy. Case Presentation. A 57-year-old male with long-standing psoriatic arthritis presented with diffuse scaling of his skin. He was being treated with adalimumab, leflunomide, and topical clobetasol, but had recently stopped taking his medications. Physical exam revealed yellow scaling covering his entire body with underlying erythema and tenderness without mucosal involvement. Labs were notable for a creatinine of 3.3 mg/dL, with no prior history of renal disease, and uric acid of 12.7 mg/dL. He was admitted to the intensive care unit given >80% of body surface area involvement and acute renal failure. Despite aggressive fluid resuscitation, renal function did not improve, and creatinine peaked at 4.61 mg/dL. Urine microscopy showed diffuse polymorphic uric acid crystals, consistent with uric acid crystal-induced nephropathy. He was started on rasburicase, urinary alkalinization, and fluids. His renal function improved dramatically; urine output, uric acid, and electrolytes normalized. He was discharged on topical clobetasol and leflunomide and started on secukinumab with little to no skin involvement. Conclusion. This case presents the rare complication of crystal-induced nephropathy in a patient with erythrodermic psoriasis. Uric acid crystal nephropathy is well described in diseases with rapid cell turnover such as tumor lysis syndrome. It is thought that rapid keratinocyte differentiation and inflammatory infiltration of psoriatic lesions produced life-threatening electrolyte abnormalities similar to tumor lysis syndrome. Early recognition of this rare complication is critical, and aggressive fluid resuscitation, urine alkalinization, and uric acid lowering agents should be administered immediately.